(untitled) (The 40th International Pupils’ Attitudes Towards Technology Conference Proceedings 2023, 2023)
STEM education is becoming more popular at the primary and secondary levels in many curricula around the world. Effective instructional STEM activities and design methods are required to ensure that students’ and teachers’ needs are being met. One potential method is the Technology Design Process (TDP): a methodology that stresses the importance of creativity, collaboration and being open to adjustments and compromises. This article reports on a case study that focused on the use of TDP to design and develop teaching-learning materials based on pendulum experiments to introduce variables and functions in mathematical context at the secondary level. The five iterative stages of TDP were integrated into the development of the course materials. Data was collected from 20 high school students who participated in a STEM activity. Both pre- and post-questionnaires were administered to the students. Additionally, a working document was used to assess the students’ understanding of abstract concepts and the TDP. The results indicate that TDP-centred activities effectively promote critical thinking, encourage questioning, and facilitate meaningful exploration of abstract concepts.